Fauna edáfica em à área de restauração florestal na região central do Rio Grande do Sul - Galvan, Camila Fonseca (2020)
Forest restoration aims to provide a gradual reconstruction of the forest, along with the resolution of biodiversity and sustainability over time, and in the medium and long term, ecological processes and functions must resemble those of the original forest. Since during and after the process of developing these methodologies, the assessment and monitoring of the recovery process of these environments must be carried out. Thus, this study was developed with the objective of evaluating the forest restoration process through mesofauna and edaphic macrofauna. The data were collected in a forest restoration area in the Quarta Colônia State Park, central region of Rio Grande do Sul, Brazil, and the methodology was developed jointly for both chapters. Monthly collections were carried out over a period of one year, where soil samples were collected at a depth of 10 cm, which were analyzed in the laboratory in two ways: a) evaluation of edaphic mesofauna using berleze funnel and b) manual collection of edaphic macrofauna. Chapter I sought to assess the influence of different vegetation coverings on the edaphic fauna in a forest restoration area. For this, an experiment was carried out in a completely randomized design with different vegetable coverings (Aroeira-pimentaira, Ingá-banana, Ipê-roxa and Native forest). Schinus terebinthifolius, Inga vera, and Handroanthus heptaphyllus are potential species for use in forest restoration because they do not differ from native forest in composition of meso and edaphic macrofauna. In Chapter II, the effect of silvicultural methods on edaphic fauna in forest restoration areas was evaluated. Three silvicultural practices (conventional forestry, low input forestry and intensive forestry) and native forest were evaluated. The silvicultural methods applied in the forest restoration area do not differ from the native forest in relation to the composition of the soil meso and macrofauna, being able to be used in the forest restoration. In this way, the results of this study allow to help the elaboration of forest restoration methods, aiming to guarantee the reconstruction of ecological processes.